Survey on Solution Providers of Hybrid Cloud Computing - Rajeswari, S. (IJRDO -Journal of Computer Science Engineering, 2016)
Cloud computing is spreading around the enterpriseworld, eliminates the requirement for setting high-costcomputing infrastructure and services for IT solutions. With itspotential, cloud computing allows numerous and varied increasein capacity and capabilities of the existing technology by the needof extending the technology across variety of clouds for intercloud communication. “Hybrid cloud” as a latest buzz word isthe deployment of contact between private, public andcommunity clouds for the necessary of application, services anddata migration. With its diverse services like SaaS, PaaS andIaaS, the hybrid cloud has made resources which was once neveravailable on scalable and demand manner. This extensive surveypaper aims to elaborate and analyze the numerous hybrid cloudcomputing service providers of which will provide thetransparency of features, profits, fitting together clouds, choosingservice providers, implementation and functionality based oninternal and external resources. Each hybrid cloud solutions ofthis era are briefed for benefiting any organizations for decidingon a hybrid cloud provider. The objective of this paper is toreview comprehensively the current hybrid cloud providers sothat interested c-level executives of the enterprises in adoption ofhybrid cloud could gain knowledge over the hybrid cloudsolution providers and will give their organization an edge overcompetitors.